A new species of Pleurothallis (Pleurothallidinae) from the southwestern Andes of Colombia in the National Natural Park Farallones de Cali - Moreno, Juan Sebastián; Galindo-Tarazona, Robinson; Alegría-Valencia, Melisa; Wilson, Mark; Zuluaga Tróchez, Alejandro (Lankesteriana: International Journal on Orchidology, 2023)
A new species of Pleurothallis from subsection Macrophyllae-Fasciculatae is described and illustrated. The new species is compared with Pleurothallis folsomii from Panama. Pleurothallis celsia is most similar to a group of species with small, yellow flowers but it can be recognized mainly by its lip, which is widely ovate, the surface and margin pilose and papillate, and the base of the glenion densely vesiculose.